Forest Fire and Biotic Interference - a Great Threat to Nilgiri Biosphere - Srivastava, Rajiv K. (Indian Forester, 2002)
The Nilgiri Biosphere, which is having countless micro flora, fauna and the germplasm of various rare, threatened and endemic species, is facing continuous pressure by one way or the other. The greatest pressure on forest is by way of forest fire, which is not only retarding the growth of existing standing vegetation but also not allowing new recruits to emerge out on the forest floor. If the process is not checked, many of the endemic flora and fauna will disappear from the biosphere reserve even before its documentation is completed.